The Ghostly Grounds: Death and Brunch (A Canine Casper Cozy Mystery-Book 2) - Sophie, Love (Lukeman Literary, 2020)
"The perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads."--Midwest Book Review (For Now and Forever)THE GHOSTLY GROUNDS: DEATH AND BRUNCH is Book #2 in a charming new cozy mystery series by bestselling author Sophie Love, author of The Inn at Sunset Harbor series, a #1 Bestseller with over 200 five-star reviews! Marie Fortune, 39, a successful dog groomer in Boston, leaves the stressful life behind and heads to a small town in coastal Maine to create a new life. She remains intent on renovating the old, historic house her great-aunt left her and giving it a new life as a B&B. Yet there was one thing she couldn't plan for: the house is haunted. Two things, actually: her great-aunt also left her a dog-and he is far from a typical dog.Other B&B owners have heard of Marie's ability to expel ghosts, and she finds herself, to her own surprise, in demand for her "services" from neighboring towns. It seems there are many B&Bs that need to have their ghosts cleansed. With her B&B failing, Marie, her trusted dog as her sidekick, has nothing to lose.But when she arrives to her first client-and someone unexpectedly dies-Marie realizes she may be in for more than she bargained for. Once again, she may have to solve the crime to save her own future.A page-turning cozy, packed with mystery, love, hauntings, travel, pets and food-anchored around a small town and a B&B in need of renovation that will capture your heart-THE GHOSTLY GROUNDS: DEATH AND BRUNCH is an un-putdownable cozy that will keep you turning pages (and laughing out loud) late into the night."The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining."--Books and Movies Reviews (For Now and Forever)Book #3 in the series-MALICE AND LUNCH-is now also available!
Keywords: Krimi, detektivky